2019
DOI: 10.25073/2588-1159/vnuer.4220
|View full text |Cite
|
Sign up to set email alerts
|

Student Skills and Employability: A Study from Students’ Perspective

Abstract: This study is aimed at evaluating the relationship among students’ skills and their employability based on surveying students using 5 point Likert scale. The survey includes 490 students whose major are foreign languages and the results show that there are differences in the level of awareness between first year students, third year students and last year students. Thanks to the data analysis, it is revealed that most students believe that the university reputation has an important role in their employability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Recent studies show that career competencies and self-perceived competencies have a relationship with career adaptability (Akkermans et al, 2018;Dumulescu et al, 2015;Monteiro et al, 2020). In terms of employability, the previous study has shown career competencies are the predictor of preparing tertiary students' employability (Faizah, 2007;Hock & Mandrinos, 2020;Hung & Phuong, 2019;Kaur et al, 2008). Despite, the relationship, graduates' establishment on career adaptability through the acquisition of self-perceived competencies could increase graduates' employability and success in their future careers.…”
Section: Self-perceived Competency Influences Career Adaptabilitymentioning
confidence: 99%
“…Recent studies show that career competencies and self-perceived competencies have a relationship with career adaptability (Akkermans et al, 2018;Dumulescu et al, 2015;Monteiro et al, 2020). In terms of employability, the previous study has shown career competencies are the predictor of preparing tertiary students' employability (Faizah, 2007;Hock & Mandrinos, 2020;Hung & Phuong, 2019;Kaur et al, 2008). Despite, the relationship, graduates' establishment on career adaptability through the acquisition of self-perceived competencies could increase graduates' employability and success in their future careers.…”
Section: Self-perceived Competency Influences Career Adaptabilitymentioning
confidence: 99%